Ferrate nanocage superstructure material as well as preparation method and application thereof
By preparing Zn-MFe2O4 nanocage superstructure material with open cage structure, the problem of building open superstructure ferrite material is solved, efficient preparation of the material and excellent gas sensitive characteristics are achieved, and it is suitable for gas sensing applications.
Patent Information
- Application Number
- CN202411892480.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The controllable construction of open superstructure ferrite materials still faces great challenges, and it is difficult to effectively utilize their inherent properties and impart new functions, especially in the field of gas sensing.
By using zinc-iron Prussian blue nanocubes as precursors, combined with Ostwald's maturation strategy and cation exchange strategy, Zn-MFe2O4 nanocage superstructure material with an open cage structure was prepared.
It has achieved efficient preparation of ferrite nanocage superstructure materials, with excellent gas sensitivity and gas sensing properties, and can show good responses to gases such as hydrogen sulfide and nitrogen dioxide.
Smart Images

Figure CN119750652A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano materials, and in particular relates to a ferrite nano cage superstructure material and a preparation method and application thereof. Background Art
[0002] Nanomaterials with complex structures, especially porous or hollow superstructured nanomaterials, have always been widely sought after by scientific researchers. Advantages such as large specific surface area, high porosity, and small grain size often give these materials unique physical and chemical properties. The large specific surface area provides abundant active sites for surface-related reactions, including adsorption / desorption, heterogeneous catalysis, and surface redox reactions. Large porosity and open framework structures can better accommodate mechanical strain, load guest substances, and promote material transport, which is very helpful for drug loading, cancer targeted therapy, etc. The solid-state diffusion distance (i.e., wall thickness or shell thickness) in porous and hollow nanomaterials is significantly smaller than the size of the corresponding solid materials, breaking through the diffusion limitations in many non-porous materials. The confinement capacity of pores and cavities also shows great promise in certain applications. More importantly, the special physical and chemical properties related to the spatial structure in open superstructured nanomaterials do not exist in their corresponding solid materials.
[0003] The careful and reasonable design of complex nanostructures can endow materials with the properties required for many current and emerging applications. Coordination polymers (CPs) have become a rapidly developing research field in the past two decades due to their unique and excellent properties, such as adjustable chemical composition, high porosity, and large specific surface area. Prussian blue (PB) and Prussian blue analogs (PBAs), as typical coordination polymers, have certain thermal and chemical stability. They can be easily converted into corresponding inorganic functional materials by pyrolysis in an inert gas atmosphere or chemical reaction with the required reagents. In particular, metal oxide nanomaterials derived from PBAs can not only maintain the morphology of the precursor, but also have adjustable chemical composition, which has obvious advantages in the field of gas sensing. For example, Guo and colleagues used PVP as a protective agent and etched PB cubes with sodium hydroxide solution to obtain PB hollow nanoboxes. By further annealing in air, Fe2O3 nanoboxes were obtained and satisfactory H2S gas-sensing performance was achieved; Xu et al. synthesized the Zn-Fe PBAs octahedral structure using PVP as a template, and used it as a precursor to prepare ZnO / ZnFe2O4 hollow nanocages for acetone gas detection; Huang's team used Zn-Fe PBAs nanocubes as precursors, and adopted a structure-induced anisotropic etching / anion exchange strategy combined with annealing process to prepare a cage-enclosed cubic ZnO / ZnFe2O4 superstructure rich in oxygen vacancies. This material can realize the detection of low-temperature trace H2S gas.
[0004] Ferrites with spinel structure (MFe2O4) have great development potential in the field of gas sensing due to their unique crystal structure and physical and chemical properties. In ferrites, some or all of the octahedral and tetrahedral coordination sites are occupied by M 2+ and Fe 3 + The cations occupy the space, forming a positive spinel or inverse spinel structure. Compared with single metal oxides, the variable multivalent cations and controllable components in spinel ferrites have significant advantages in improving gas sensing performance.
[0005] Fe, Co, Ni, Cu, and Zn are elements in the same period with adjacent atomic numbers. However, the five transition cations have different valence states, occupy the central position of the octahedron / tetrahedron, and have different gas adsorption and catalytic properties. 2+ Spinel ferrites (MFe2O4) with (M = Co, Ni, Cu and Zn) exhibit different n / p-type semiconductor properties, different band gaps and oxygen adsorption capabilities. It is necessary to systematically study the relationship between the cation substitution effect and the gas sensing properties of ferrite materials. In addition, traditional ferrites are mostly solid or hollow polyhedral structures, and open superstructured ferrites with higher specific surface areas may provide unexpected advantages for various applications including gas sensing.
[0006] However, the controllable construction of open superstructured ferrites still faces great challenges. In order to better utilize the intrinsic properties of these superstructured ferrites and endow them with new functions, more research efforts are needed to develop new and facile synthetic strategies. Summary of the invention
[0007] The purpose of the present invention is to provide a ferrite nanocage superstructure material and a preparation method and application thereof; by regulating the micro-nano structure of the composite material, an open cage nanostructure is obtained to improve the gas-sensing properties.
[0008] The technical solution adopted by the present invention is as follows:
[0009] A method for preparing a ferrite nanocage superstructure material, the preparation method comprising the following steps:
[0010] (1) dissolving a zinc salt in dilute hydrochloric acid, adding an aqueous solution of potassium ferrocyanide thereto, stirring until the solution becomes a yellow suspension, standing and aging at 10 to 95° C. for 2 to 36 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocube precursor material, and then dispersing the precursor material in deionized water, standing and aging at 15 to 45° C. for 24 to 120 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocage;
[0011] (2) Dispersing zinc-iron Prussian blue nanocages in a dilute hydrochloric acid solution, adding metal salt, stirring evenly, standing and reacting at 50-120° C. for 6-48 hours, filtering, washing, and drying, and then annealing at 300-500° C. for 1-5 hours to obtain a Zn-MFe2O4 nanocage superstructure material, wherein M is one of Fe, Co, Ni, Cu, and Zn.
[0012] In step (1), the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate.
[0013] In step (1), the molar ratio of potassium ferrocyanide to zinc salt is 1:1.
[0014] In step (1), the concentration of the potassium ferrocyanide aqueous solution is 0.1-2.0 mol / L; the concentration of the zinc salt in dilute hydrochloric acid is 0.1-2.0 mol / L; and the concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.
[0015] In step (2), the metal salt is any one of ferrous sulfate, ferrous chloride, ferrous nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, cupric sulfate, cupric chloride, cupric nitrate, zinc sulfate, zinc chloride, and zinc nitrate.
[0016] In step (2), the ratio of the zinc-iron Prussian blue nanocage to the metal salt is 0.1-0.5 g: 0.5-1.5 mmol.
[0017] In step (2), the concentration of the zinc-iron Prussian blue nanocage in dilute hydrochloric acid is 1.0-5.0 mg / mL; the concentration of the dilute hydrochloric acid is 0.1-1.2 M.
[0018] In step (2), the static reaction condition is preferably 50-70° C. for 8-12 h.
[0019] In step (2), the annealing condition is preferably 320-400° C. annealing for 2-3 h.
[0020] In step (2), the heating rate to the specified annealing temperature is 1 to 5°C / min, preferably 1 to 2°C / min.
[0021] The invention also provides a ferrite nano cage superstructure material prepared by the preparation method.
[0022] The present invention also provides the application of the ferrite nanocage superstructure material in a gas sensor, wherein Zn-Fe3O4, Zn-CoFe2O4, and Zn-CuFe2O4 have a high sensitivity response to hydrogen sulfide, and Zn-NiFe2O4 has a high sensitivity response to nitrogen dioxide gas.
[0023] In the preparation method disclosed by the present invention, zinc iron Prussian blue nanocubes which are easy to prepare are used as precursors, zinc iron Prussian blue nanocages are obtained through aging, zinc iron Prussian blue analog nanocages are obtained through ion exchange, and ferrite nanocage superstructure materials are obtained after high-temperature calcination.
[0024] Some of the chemical reaction formulas involved in the reaction process are shown below:
[0025] 3Zn 2+ +3[Fe(CN)6] 3- →Zn3[Fe(CN)6]2(1)
[0026] 4Fe 2+ +O2+4H + →4Fe 3+ +2 H2O(2)
[0027] 2Fe 3+ +6Fe 2+ +3Zn3[Fe(CN)6]2→2Fe4[Fe(CN)6]3+9Zn 2+ (3)
[0028] 3Co 2+ +2[Fe(CN)6] 3- +H2O→Co3[Fe(CN)6]2(4)
[0029] 3Ni 2+ +2[Fe(CN)6] 3- +10 H2O→Ni3[Fe(CN)6]2·10 H2O(5)
[0030] 10Cu 2+ +7[Fe(CN)6] 3- +19 H2O→10Cu[Fe(CN)6] 0.7 1.9 H2O(6)
[0031] In the present invention, the Ostwald ripening strategy is adopted to control the preparation of Zn-Fe PBAs nanocages with special morphological structures in the absence of templates / protective agents, and a series of M-Fe PBAs (M = Fe, Co, Ni, Cu, Zn) nanocage superstructures are prepared by the cation exchange strategy. Specifically, the density distribution of a single Zn-Fe PBAs nanocube is changed by the Ostwald ripening mechanism, so that a density defect is generated in its central part, and a passivation layer is formed on its surface and corners. By controlling the ripening time, the Zn-Fe PBAs nanobox and nanocage can be controlled. In addition, combined with the unique structural properties of the Zn-Fe PBAs nanocage, a series of M-Fe PBAs (M = Fe, Co, Ni, Cu, Zn) open nanocage superstructures are successfully prepared by the metal cation exchange strategy.
[0032] Compared with previously reported nanocages, this strategy can prepare a series of Zn-MFe2O4 nanocages (M=Fe, Co, Ni, Cu, Zn) in a simple, green and controllable manner without complicated preparation procedures. After annealing in air, the M-Fe PBAs nanocage superstructure is further transformed into the corresponding metal oxide, and the morphology and structure are well maintained. In terms of gas sensing performance, the completely open spatial structure can produce more defects, which is not only conducive to exposing more active sites, but also conducive to the adsorption and diffusion of target gases on the surface of the material. The ultra-thin wall thickness also shortens the distance that carriers migrate inside the nanocage superstructure. These advantages make these metal oxide nanocage superstructures have excellent gas sensing performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a SEM image of the zinc iron Prussian blue nanocube precursor prepared in Example 1;
[0034] Figure 2 This is the XRD pattern of the zinc iron Prussian blue nanocube precursor prepared in Example 1;
[0035] Figure 3 This is a SEM image of the zinc-iron Prussian blue nanocage prepared in Example 1;
[0036] Figure 4 This is a SEM image of the Prussian blue analog nanocage prepared in Example 1;
[0037] Figure 5 This is a SEM image of the Zn-Fe3O4 nanocage superstructure material prepared in Example 1;
[0038] Figure 6 The XRD pattern of the Zn-Fe3O4 nanocage superstructure material prepared in Example 1;
[0039] Figure 7 This is the EDS image of the Zn-Fe3O4 nanocage superstructure material prepared in Example 1;
[0040] Figure 8 This is a SEM image of the Prussian blue analog nanocage prepared in Example 2;
[0041] Fig. 9 This is a SEM image of the Zn-CoFe2O4 nanocage superstructure material prepared in Example 2;
[0042] Fig.10 This is the XRD pattern of the Zn-CoFe2O4 nanocage superstructure material prepared in Example 2;
[0043] Fig.11 Element distribution diagram of the Zn-CoFe2O4 nanocage superstructure material prepared in Example 2;
[0044] Fig.12 This is the EDS image of the Zn-CoFe2O4 nanocage superstructure material prepared in Example 2;
[0045] Fig.13 This is a SEM image of the Prussian blue analog nanocage prepared in Example 3;
[0046] Fig.14 This is a SEM image of the Zn-NiFe2O4 nanocage superstructure material prepared in Example 3;
[0047] Fig.15 This is the XRD pattern of the Zn-NiFe2O4 nanocage superstructure material prepared in Example 3;
[0048] Fig.16 This is the EDS image of the Zn-NiFe2O4 nanocage superstructure material prepared in Example 3;
[0049] Fig.17 This is a SEM image of the Prussian blue analog nanocage prepared in Example 4;
[0050] Fig.18 This is a SEM image of the Zn-CuFe2O4 nanocage superstructure material prepared in Example 4;
[0051] Fig.19 The XRD pattern of the Zn-CuFe2O4 nanocage superstructure material prepared in Example 4;
[0052] Fig. 20 This is the EDS image of the Zn-CuFe2O4 nanocage superstructure material prepared in Example 4;
[0053] Fig.21The response sensitivity of the Zn-Fe3O4, Zn-CoFe2O4, Zn-NiFe2O4 and Zn-CuFe2O4 nanocage superstructure material sensors prepared in the examples to 10ppm H2S and 100ppm different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.) at an operating temperature of 140°C. DETAILED DESCRIPTION
[0054] The present invention is described in detail below with reference to the embodiments.
[0055] The reaction container used in step (2) in each embodiment is a beaker, and the mouth of the beaker is covered with plastic wrap during heating.
[0056] Example 1
[0057] A method for preparing a Zn-Fe3O4 nanocage superstructure material comprises the following steps:
[0058] (1) Potassium ferrocyanide was dissolved in deionized water to prepare a 1000 mL, 0.1 M potassium ferrocyanide solution; zinc chloride was dissolved in dilute hydrochloric acid to prepare a 1000 mL, 0.1 M zinc chloride solution; the potassium ferrocyanide solution was added to the zinc chloride solution under magnetic stirring at a speed of 120 rpm, and then the stirring was continued at room temperature for 30 min to obtain a mixed suspension, which was allowed to stand for 12 h at 80° C. to obtain a yellow precipitate, and the yellow precipitate was filtered, washed, and dried at 80° C. for 8 h to obtain a zinc-iron Prussian blue nanocube precursor; its SEM image is shown as follows Figure 1 As shown in the figure, it can be seen that it is a uniform cubic block; its XRD pattern is as follows Figure 2 As shown, the diffraction pattern proves that the prepared zinc-iron Prussian blue has a strong peak and high purity.
[0059] The obtained zinc iron Prussian blue nanocubes were aged in deionized water for 3 days, then fully washed with anhydrous ethanol and dried. The obtained product was zinc iron Prussian blue nanocages, and its SEM image is shown in Figure 3 shown.
[0060] (2) Take 0.2g zinc iron Prussian blue nanocages and disperse them in 100mL of 0.1M dilute hydrochloric acid, add 1mmol FeCl2 and stir vigorously for 30min, then transfer the beaker into an 80℃ oven for 8h. Wash the blue precipitate with deionized water and ethanol and dry it to obtain Prussian blue analog nanocages, the SEM image of which is shown in the figure. Figure 4 shown.
[0061] (3) The obtained Prussian blue analog nanocage sample was transferred to a muffle furnace, heated to 500°C at a heating rate of 1°C / min and annealed for 1 h to obtain a Zn-Fe3O4 open nanocage superstructure material, as shown in the SEM image. Figure 5 Its XRD pattern is shown in Figure 6 As shown, it can be seen that the product is zinc-doped Fe3O4. The product EDS image is as follows Figure 7 As shown, it can be seen that the product contains zinc, iron and oxygen elements, and the silicon element comes from the silicon substrate.
[0062] Example 2
[0063] A method for preparing a Zn-CoFe2O4 open nanocage superstructure composite material comprises the following steps:
[0064] (1) Same as step (1) in Example 1.
[0065] (2) Take 0.2g zinc iron Prussian blue nanocages and disperse them in 100mL of 0.6M dilute hydrochloric acid, add 1mmol CoCl2 and stir vigorously for 30min, then transfer to an 80℃ oven and keep warm for 8h. The blue precipitate is thoroughly washed and dried with deionized water and ethanol to obtain Prussian blue analog nanocages, whose SEM image is shown in the figure. Figure 8 shown.
[0066] (2) The obtained Prussian blue analog nanocage sample was transferred to a muffle furnace and heated to 400°C at a heating rate of 2°C / min and annealed for 2 h to obtain a Zn-CoFe2O4 open nanocage superstructure. The SEM image is shown in FIG. Fig. 9 Its XRD pattern is shown in Fig.10 The element distribution diagram and EDS results of the prepared Zn-CoFe2O4 nanocage superstructure material are shown in Fig.11 and Fig.12 As shown, it can be seen that the product contains zinc, cobalt, iron and oxygen elements, and the above elements are evenly distributed on the nanocage, and the silicon element comes from the silicon substrate.
[0067] Example 3
[0068] A method for preparing a Zn-NiFe2O4 open nanocage superstructure composite material comprises the following steps:
[0069] (1) Same as step (1) in Example 1.
[0070] (2) Take 0.2g zinc iron Prussian blue nanocages and disperse them in 100mL of 0.9M dilute hydrochloric acid, add 1mmol NiCl2 and stir vigorously for 30min, then transfer to an 80℃ oven and keep warm for 8h. The blue precipitate is thoroughly washed and dried with deionized water and ethanol to obtain Prussian blue analog nanocages, the SEM image of which is shown in Fig.13 shown.
[0071] (3) The obtained Prussian blue analog nanocage sample was transferred to a muffle furnace, heated to 350°C at a heating rate of 2°C / min and annealed for 3 h to obtain a product of Zn-NiFe2O4 open nanocage superstructure material, the SEM image of which is shown in FIG. Fig.14 The product XRD pattern is shown in Fig.15 As shown, its EDS diagram is as follows Fig.16 As shown, the product contains zinc, iron, nickel and oxygen elements, and the product is zinc-doped NiFe2O4. The silicon element in the EDS image comes from the silicon substrate.
[0072] Example 4
[0073] A method for preparing a Zn-CuFe2O4 open nanocage superstructure composite material comprises the following steps:
[0074] (1) Same as step (1) in Example 1.
[0075] (2) Take 0.2g zinc iron Prussian blue nanocages and disperse them in 100mL of 1.2M dilute hydrochloric acid, add 1mmol CuCl2 and stir vigorously for 30min, then transfer to an 80℃ oven and keep warm for 8h. The blue precipitate is thoroughly washed and dried with deionized water and ethanol to obtain Prussian blue analog nanocages, whose SEM image is shown in the figure. Fig.17 shown.
[0076] (3) The obtained Prussian blue analog nanocage sample was transferred to a muffle furnace, heated to 300°C at a heating rate of 5°C / min and annealed for 5 h to obtain a product, which was a Zn-CuFe2O4 open nanocage superstructure material. The SEM image of the product is shown in FIG. Fig.18 The product XRD pattern is shown in Fig.19 As shown, its EDS diagram is as follows Fig. 20 As shown, the product contains zinc, iron, copper and oxygen elements, and the product is zinc-doped CuFe2O4. The silicon element in the EDS image comes from the silicon substrate.
[0077] Application Example 1
[0078] Application of ferrite open nanocage superstructure composites in gas sensors
[0079] The ferrite open nanocage superstructure composite material prepared in Examples 1 to 4 is dispersed in anhydrous ethanol, and then evenly coated on a ceramic tube with electrodes to make a gas sensor, dried at 50°C for 2 hours, and then heat treated at 200°C for 2 hours. Then, a small nickel-chromium alloy coil is placed in the tube as a heater to provide the sensor with an operating temperature. The sensor is aged at 300°C for 48 hours, and then different volatile organic gases are tested at the operating temperature. The specific test operation steps are: use a syringe to inject a certain amount of organic vapor into the sensor test box, wait for about 2 minutes, and after the sensor output response value stabilizes, dry air is introduced into the test box, and the sensor output response gradually recovers. Use an electrochemical workstation and a computer to test and record the output response value of the sensor in dry air and with the target gas. The sensor's sensitivity to gas response is defined as S=R a / R g (reducing gas), R a is the resistance of the sensor in dry air, R g is the resistance of the sensor in the test gas.
[0080] Performance test studies have shown that the prepared ferrite open nanocage superstructure composite material has a good sensitive response to common toxic and harmful organic gases in the air, such as Fig.21 As shown in the figure, it can be seen that compared with different types of VOCs (including ethanol, isopropanol, acetone, benzene, toluene, n-butanol, methanol and ammonia, etc.), the ferrite open nanocage superstructure materials Zn-Fe3O4, Zn-CoFe2O4, and Zn-CuFe2O4 prepared by this method show good selectivity for hydrogen sulfide, and the Zn-NiFe2O4 prepared by this method shows good selectivity for nitrogen dioxide.
[0081] The detailed description of a ferrite nanocage superstructure material and its preparation method and application with reference to the above-mentioned embodiments is illustrative rather than restrictive, and several embodiments can be listed according to the limited scope. Therefore, changes and modifications without departing from the overall concept of the present invention should fall within the scope of protection of the present invention.
Claims
1. A method for preparing a ferrite nanocage superstructure material, characterized in that: The preparation method comprises the following steps: (1) dissolving a zinc salt in dilute hydrochloric acid, adding an aqueous solution of potassium ferrocyanide thereto, stirring until the solution becomes a yellow suspension, standing and aging at 10 to 95° C. for 2 to 36 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocube precursor material, and then dispersing the precursor material in deionized water, standing and aging at 15 to 45° C. for 24 to 120 hours, filtering, washing, and drying to obtain a zinc iron Prussian blue nanocage; (2) Dispersing zinc-iron Prussian blue nanocages in a dilute hydrochloric acid solution, adding metal salt, stirring evenly, standing and reacting at 50-120° C. for 6-48 hours, filtering, washing, and drying, and then annealing at 300-500° C. for 1-5 hours to obtain a Zn-MFe2O4 nanocage superstructure material, wherein M is one of Fe, Co, Ni, Cu, and Zn.
2. The preparation method according to claim 1, characterized in that: In step (1), the zinc salt is one or more of zinc chloride, zinc sulfate, zinc acetate and zinc nitrate.
3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the molar ratio of potassium ferrocyanide to zinc salt is 1:
1.
4. The preparation method according to claim 1 or 2, characterized in that: In step (1), the concentration of the potassium ferrocyanide aqueous solution is 0.1-2.0 mol / L; the concentration of the zinc salt in dilute hydrochloric acid is 0.1-2.0 mol / L; and the concentration of the dilute hydrochloric acid is 0.1-1.2 mol / L.
5. The preparation method according to claim 1, characterized in that: In step (2), the metal salt is any one of ferrous sulfate, ferrous chloride, ferrous nitrate, cobalt sulfate, cobalt chloride, cobalt nitrate, nickel sulfate, nickel chloride, nickel nitrate, cupric sulfate, cupric chloride, cupric nitrate, zinc sulfate, zinc chloride, and zinc nitrate.
6. The preparation method according to claim 1, 2 or 5, characterized in that: In step (2), the ratio of the zinc-iron Prussian blue nanocage to the metal salt is 0.1-0.5 g: 0.5-1.5 mmol.
7. The preparation method according to claim 1, 2 or 5, characterized in that: In step (2), the concentration of the zinc-iron Prussian blue nanocage in dilute hydrochloric acid is 1.0-5.0 mg / mL; the concentration of the dilute hydrochloric acid is 0.1-1.2M.
8. The preparation method according to claim 1, 2 or 5, characterized in that: In step (2), the heating rate to the specified annealing temperature is 1 to 5°C / min.
9. The ferrite nanocage superstructure material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the ferrite nanocage superstructure material as claimed in claim 9 in a gas sensor.
Citation Information
Patent Citations
Preparation method of nano hollow structure prussian blue and analogues thereof
CN108133832A
Preparation method and application of pseudo-cubic ferric oxide nanocage with multilevel structure
CN108285175A
Preparation method of sawtooth-like nickel-cobalt-iron PBA (prussian blue analogue) sintered oxide nanomaterial
CN109437338A
Porous Ni(OH)2 nano cage and preparation method thereof
CN109592721A
Hollow nano cage composite material and preparation method and application thereof
CN110310838A
Cited By
Fe2O3 nanotube / zinc ferrite open nanocage superstructure composite material as well as preparation method and application thereof
CN119750654A
A Fe2O3 nanotube / zinc ferrite open nanocage superstructure composite material, its preparation method and application
CN119750654B